Efficient NH3‑Tolerant Nickel-Based Hydrogen Oxidation Catalyst for Anion Exchange Membrane Fuel Cells - Wang, Ye-Hua; Gao, Fei-Yue; Zhang, Xiao-Long; Yang, Yu; Liao, Jie; Niu, Zhuang-Zhuang; Qin, Shuai; Yang, Peng-Peng; Yu, Peng-Cheng; Sun, Mei; Gao, Min-Rui (Journal of the American Chemical Society, 2023)
Converting hydrogen chemical energy into electrical energy by fuel cells offers high efficiencies and environmental advantages, but ultrapure hydrogen (over 99.97%) is required; otherwise, the electrode catalysts, typically platinum on carbon (Pt/C), will be poisoned by impurity gases such as ammonia (NH3). Here we demonstrate remarkable NH3 resistivity over a nickel–molybdenum alloy (MoNi4) modulated by chromium (Cr) dopants. The resultant Cr-MoNi4 exhibits high activity toward alkaline hydrogen oxidation and can undergo 10,000 cycles without apparent activity decay in the presence of 2 ppm of NH3. Furthermore, a fuel cell assembled with this catalyst retains 95% of the initial peak power density even when NH3 (10 ppm)/H2 was fed, whereas the power output reduces to 61% of the initial value for the Pt/C catalyst. Experimental and theoretical studies reveal that the Cr modifier not only creates electron-rich states that restrain lone-pair electron donation but also downshifts the d-band center to suppress d-electron back-donation, synergistically weakening NH3 adsorption.